Computer-aided extra-pulmonary tuberculosis diagnosis using image processing and HMLP network - Muhammad Khusairi Osman (School of Mechatronic Engineering, University Malaysia Perlis, 2014)
This research proposes a method for automatic detection of TB bacilli in tissue sections for EPTB diagnosis.